1997
DOI: 10.1021/bi971419d
|View full text |Cite
|
Sign up to set email alerts
|

Intersubunit Communication in Hybrid Hexamers of K89L/A163G/S380A and C320S Mutants of Glutamate Dehydrogenase fromClostridium symbiosum

Abstract: The triple mutant K89L/A163G/S380A (inactive with glutamate but active with L-Nle and L-Met) and C320S (fully active with glutamate, entirely inactive with L-Nle and L-Met, and also lacking reactive cysteine) mutant of glutamate dehydrogenase (EC 1.4.1.2) of Clostridium symbiosum could be completely denatured by urea with the loss of structure and activity. The mutants denatured by urea could be reassociated to give stable hexamers with recovery of activity of approximately 67% by dilution in 0.1 M potassium p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Parallel studies of urea‐induced unfolding of both mutant proteins revealed no major differences in behaviour, with 4 m urea sufficient for the unfolding of both within 30 min. These results have been reported previously for C320S [20]. Neither of the two forms of coenzyme, NAD + and NADH, was able to protect effectively against denaturation; both proteins were almost completely resistant to 4 m urea in the presence of 2‐oxoglutarate (50 m m ) or in the combined presence of NADH/glutamate (2 m m /50 m m ) or NAD + /2‐oxoglutarate (2 m m /50 m m ), and glutamate (50 m m ) alone gave 50% protection.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Parallel studies of urea‐induced unfolding of both mutant proteins revealed no major differences in behaviour, with 4 m urea sufficient for the unfolding of both within 30 min. These results have been reported previously for C320S [20]. Neither of the two forms of coenzyme, NAD + and NADH, was able to protect effectively against denaturation; both proteins were almost completely resistant to 4 m urea in the presence of 2‐oxoglutarate (50 m m ) or in the combined presence of NADH/glutamate (2 m m /50 m m ) or NAD + /2‐oxoglutarate (2 m m /50 m m ), and glutamate (50 m m ) alone gave 50% protection.…”
Section: Resultssupporting
confidence: 91%
“…Subunits unable to bind coenzyme are generated by modifying with 5,5′‐dithiobis (2‐nitrobenzoic acid (DTNB), which reacts exclusively with C320 in the vicinity of the coenzyme binding site [15–17]; subunits that are still catalytically active but unable to accept glutamate as a substrate are made by site‐directed mutagenesis of the binding pocket for the substrate side‐chain [18]. Enzyme subunits thus disabled in the binding of either substrate have been used in in vitro hybridization experiments aimed at dissecting the relationship between the apparent cooperativity in the binding of glutamate and of NAD + [19–22]. The present study aims further to discover whether such apparent cooperativity can be mediated through catalytically inactive subunits that are otherwise potentially competent with regard to the binding of substrates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The C320S mutant shows very similar behaviour, with an h value of 5.2 [18]. The sigmoidal response of the DTNB-treated 5 : 1 (WT :C320S) hybrid to glutamate at high pH persisted (h l 3.6), since, though inactive, the chemically modified WT subunits can presumably still bind glutamate [20].…”
Section: Introductionmentioning
confidence: 93%
“…Defined inter-subunit hybrids have been made by combining chemical modification and site-directed mutagenesis [17][18][19][20]. Using the Cys320Ser mutant (C320S) [21], which is unable to react with 5,5h-dithiobis(2-nitrobenzoate) (DTNB), as the source of the single active subunit in each hexamer, 5 : 1 hybrids were made both with wild-type (WT) GDH [20] and with the triple mutant Lys89Ser\Ala163Gly\Ser380Ala (K89L\A163G\ S380A) [18], which contributes subunits that are active with -methionine and -norleucine and catalytically inactive towards glutamate [22,23], but are nevertheless still able to bind this amino acid [18]. In both cases, after treatment with DTNB [24,25], the hexamers have only one subunit (C320S) able to bind NAD + , and show classical Michaelis-Menten kinetics with regard to NAD + , unlike the C320S homohexamer [18] or WT GDH [6], which both show marked deviation from classical kinetics.…”
Section: Introductionmentioning
confidence: 99%